Improving the creation of digital cards of nuclear power plants on the basis of MZM - Abduazizov Abduvali; Allanazarov Olimjon Rakhmonovich; Raximov Sherzod Shavkatovich; Nizomova Albina Talgatovna; Koraboyev Khusnidin Abdishukurovich (Zien Journals, 2024)
In this article, nuclear power plants are numerical improvement and geospatial mapping based on MZM emphasis is placed on placement issues. Nuclear power plants 1:10000 and 1 within a radius of 30 km of the planned construction area 1: 25000 from drones when updating scale cards The materials obtained were widely used in this data primary and the rest are auxiliary materials
Keywords: Cartographic; remote sensing materials; UAVs